Immobilization of an acid–base cooperative catalyst on MCM-41 as a heterogeneous approach for the asymmetric cyanoethoxycarbonylation of isatins. (29th August 2019) - Ansari, Amamudin; Patel, Parth; Kumar, Gaurav; Khan, Noor-ul H.
Abstract : Heterogenization of chiral quinine-thiourea catalyst for enantioselective cyanation reaction. The catalyst is found to be efficient and recyclable up to five times with retention of its catalytic activity. Abstract : A novel, highly efficient and recyclable quinine thiourea-based catalyst grafted on MCM-41 mesoporous silica was synthesized and explored as a heterogeneous catalyst for the cyanoethoxycarbonylation of isatin. MCM-41 has a high specific surface area and pore volume that allow maximum catalyst incorporation into pores. The catalyst was characterized by various sophisticated analytical techniques, including X-ray powder diffraction (XRD), TEM, thermogravimetric analysis (TGA), FTIR, BET surface area analysis, and 13 C CP-MAS NMR spectroscopy. The catalyst proved efficient for various isatin derivatives to provide good yields with enantioselectivity of up to 98%. Further, the catalyst works well for up to five cycles without losing its activity.